2016
DOI: 10.1016/j.nima.2016.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Apparatus and method for plasma processing of SRF cavities

Abstract: An apparatus and a method are described for plasma etching of the inner surface of superconducting radio frequency (SRF) cavities. Accelerator SRF cavities are formed into a variable-diameter cylindrical structure made of bulk niobium, for resonant generation of the particle accelerating field. The etch rate non-uniformity due to depletion of the radicals has been overcome by the simultaneous movement of the gas flow inlet and the inner electrode. An effective shape of the inner electrode to reduce the plasma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…The experimental setup closely resembles that of the previous work reported by Upadhyay et al [3][4][5][6][7][8][9] The main differences are upgrades in the pumping system. The plasma chamber is evacuated using a combination of a Pfeiffer/Adixen ATH-500MT turbomolecular pump and a Leybold Trivac D65 BCS PFPE rough pump.…”
Section: A Discharge Chamber and Experimental Conditionssupporting
confidence: 52%
See 2 more Smart Citations
“…The experimental setup closely resembles that of the previous work reported by Upadhyay et al [3][4][5][6][7][8][9] The main differences are upgrades in the pumping system. The plasma chamber is evacuated using a combination of a Pfeiffer/Adixen ATH-500MT turbomolecular pump and a Leybold Trivac D65 BCS PFPE rough pump.…”
Section: A Discharge Chamber and Experimental Conditionssupporting
confidence: 52%
“…IARIE techniques have entered competitively into the development of resonant superconductive radio-frequency (SRF) niobium (Nb) cavities used in high energy particle accelerators. [3][4][5][6][7][8][9] The aim is to complement or replace the "wet" acid processes that are commonly used to remove surface impurities that limit the performance of the bulk superconductive medium and to create a smooth surface with the reduction of grain boundaries and pits. 10 By adopting the same basic principles used on the semiconductor nanotechnology, IARIE shows promise in the preparation of SRF cavities for use in particle accelerators by potentially achieving similar or better superconducting properties as compared to current methods while decreasing costs, processing time, and manpower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma processing was proven as an effective method for processing the surfaces in research areas of semiconductor and medical applications. Recently developed technology might lead to an efficient method of processing the accelerating cavities [2]. Although the effect of plasma on the various accelerator materials has been studied so far, further experimental research is needed to determine the SEE from the cavity surface in order to provide comprehensive data for simulations of cavity performance.…”
Section: Secondary Electron Emission (See) Definition Of Secondary Ementioning
confidence: 99%
“…Recently, two research groups have reported their progress in the application of plasma processing techniques for accelerating cavities. The first group focused on developing the experimental setup that could possibly replace the BCP and ECP methods in surface etching of the niobium SRF cavity[2]. They reported using the ionized Ar/Cl2 gas mixture to remove significant quantities of niobium from ring type samples.…”
mentioning
confidence: 99%